Testemunhos da modernidade: arquitetura moderna em Chapecó, SC - Souza, Edgar de (2023)
Although Brazil was the first country in the world to implement actions aimed at safeguarding its modern architecture, there is a scarcity of studies on modern architectural, urban and landscape production outside the large centers, limited to the study capitals. In this sense, the present work, carried out in the Graduate Program in Cultural Heritage, is part of the thematic area of “Architecture and Material Heritage” and the research line of “Preservation of Material Heritage”, taking as its object of study the diffusion of modern principles in the urban architecture of the municipality of Chapecó, located in the western region of the state of Santa Catarina, between 1960 and 1990. the main objective is to understand how the ideals of modern architecture were incorporated in Chapecó - in view of the historical, socioeconomic and political conditions. More specifically, it is intended to map the actions undertaken, identify the promoting agents, analyze the resulting architecture, as well as register such production in order to list the most significant examples for historical preservation. Initially, the study will be divided into six methodological steps: bibliographic research; documentary research; iconographic research; field research; data analysis and final structuring. Through an empirical survey carried out in the urban space of Chapecó and subsequent verification in the stages of bibliographic, iconographic and documentary research, it was possible to recognize the buildings of modern aesthetics materialized in Chapecó. Thus, a total of ninety (90) buildings with modernist aesthetics were counted, distributed in eleven (11) neighborhoods and grouped into five (5) different typologies. Subsequently, eight (8) examples of the set of modern buildings inventoried in Chapecó were selected and analyzed, which, due to their values, especially technical and historical, have potential for heritage preservation. As the main impacts on the urban chapecoense landscape, we can mention the implementation of new typologies, especially public ones, as well as the use of new forms and materials that started to compose the local constructive repertoire, contributing, especially, to the verticalization of local buildings. Through this work, it was intended to contribute to the field of Brazilian modern architecture in the southern region of Brazil, going beyond the generalizations established from the state capitals, seeking to understand its importance in the process of the historical construction of Chapecó.